Resveratrol may reduce oxidative stress and apoptosis in doxorubicin-induced cardiotoxicity by regulating meteorin-like and TRPM2 levels - Kaya, Sercan; Yalçın, Tuba; Kuloğlu, Tuncay (Springer Science and Business Media Deutschland GmbH, 2023)
Doxorubicin (DOX) is an anthracycline antibiotic with a chemotherapeutic effect and has well-known cardiotoxic side effects. This study aimed to determine potential cardioprotective mechanisms of different doses of resveratrol (RES) in a DOX-induced cardiotoxic rat model. In the study, 42 Sprague–Dawley male rats were randomly divided into six groups (n = 7). The control group (n = 7) was given only ad libitum feed and water; the DOX group (n = 7) was administered DOX intraperitoneally (i.p) at a dose of 15 mg/kg at the beginning of the experiment. The DOX + RES I (n = 7) and DOX + RES II (n = 7) groups were administered RES i.p at doses of 1 mg/kg/day and 5 mg/kg/day, respectively, after administering 15 mg/kg DOX. The RES I (n = 7) and RES II (n = 7) groups were administered RES i.p at doses of 1 mg/kg/day and 5 mg/kg/day, respectively. Cardiac tissues collected upon completion of experimental procedures were used for biochemical, histopathological, and immunohistochemical evaluations. It was determined that RES administration may have an antiapoptotic effect by regulating apoptotic protein activities and an antioxidant effect by regulating oxidative stress parameters in DOX-induced cardiotoxicity. It was also observed that RES may regulate the levels of Meteorin-Like (MTRNL), which plays a role in energy metabolism, and the immunoreactivity of the transient receptor potential melastatin 2 (TRPM2) channel, which has a role in cellular ion homeostasis. RES may improve cardiac tissue damage by showing antiapoptotic and antioxidant effects against DOX-induced cardiotoxicity. Furthermore, MTRNL and TRPM2 ion channels may play a role in DOX-induced cardiotoxicity. © 2023, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.
Keywords: Cardiotoxicity; Doxorubicin; Melastatin 2; Meteorin-like; Resveratrol; Transient receptor potential